Papillary adenocarcinoma in situ of the skin: report of four cases - Shen Cheng; Masoud Asgari (Mattioli1885, 2014)
Although rare isolated cases of adenocarcinoma in situ of skin have been reported in the literature, adenocarcinoma in situ of skin as a concept and as a diagnostic category has not been established in the field of dermatopathology. In this work, four cases of papillary adenocarcinoma in situ of the skin are presented. In addition, the notion that lesions previously reported in the medical literature under the term of "papillary eccrine adenoma" are actually adenocarcinoma in situ is discussed.